Comprehensive tectonics : technical building assemblies from the ground to the sky - Gregory, Alexis (New York : Routledge, 2019)
Comprehensive Tectonics considers building construction assemblies holistically to help you make architectural detailing decisions from the earth to the sky. Seven case studies from architecture firms such as Perkins + Will, Lake Flato, and Olson Kundig Architects include more than 250 color images showing component details, building sections, wall sections, and floor plans. For each project, the architects explain their design intent and the reasons for their material and tectonic choices, to help you form your own strategies. This book will provide you with assistance by its ease of use with legible keys, scales, and reference images. Its key insights about why the firm chose certain materials will allow you to create your own process for utilizing building construction assemblies. Comprehensive Tectonics aims to give you a more comprehensive overviewof building construction assembles to aid in the creation of well-designed and well-developed architecture. Including a glossary and guide for how to determine assembly, this book makes a welcome desk reference and is an ideal addition for students in architecture integrated studios dealing with structures and materials and is also a useful addition for professional architects.
7 Shanghai Nature Museum: Shanghai, China, Perkins + WillArchitect's Design Intent and Reasoning Behind Material and Tectonic Choices; Guide: How to Determine Assembly; Afterword; Notes; Image and Drawing Credits; Images; Drawings; Glossary of Terms and Materials; Index
OCLC-licensed vendor bibliographic record.
Keywords: Architecture -- Details -- Case studies; Building materials -- Case studies; ARCHITECTURE / Methods & Materials; ARCHITECTURE / Design & Drafting; ARCHITECTURE / General